Unsteady flow of silica nanofluid over a stretching cylinder with effects of different shapes of nanoparticles and Joule heating - Ramzan Ali (17541780) (2024)
Indeed, nanofluids have garnered significant interest in various fields due to their numerous advantages and potential ap-plications. The appeal of SiO2 nanofluid, in particular, lies in its low preparation cost, simple production process, controlled chemistry, environmental safety and its exceptional ability to be homogeneously suspended in the base fluid, which makes it a promising candidate for a variety of applications. In this study, we investigate the flow analysis of a water based silicon dioxide nanofluid, passing over a stretched cylinder while subjected to a continuous magnetic field, including Joule heating effects. The research involves the development of a mathematical model and the formulation of governing equations represented as partial differential equations. These equations are subsequently transformed into non-linear ordinary differential equations through suitable transformations. To obtain a numerical solution, the MATLAB bvp4c solver technique is em-ployed. The study investigates the implications of dimensionless parameters on velocity and thermal distributions. It is observed that the velocity distribution f'(η) exhibits a direct relationship with the volumetric fraction ϕ and an inverse relationship with the unsteadiness parameter S, the magnetic parameter M, and the temperature distribution θ(η) shows an enhancement for the increasing ϕ and M, as well as the Eckert number. However, it declines against S and the Prandtl number. The results for local Nusselt number and skin frictions are depicted in Tables. Other Information Published in: Archives of Thermodynamics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.24425/ather.2024.151222